2021
DOI: 10.31234/osf.io/bwp6f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physiological Indicators of Driver Workload During Car-Following Scenarios and Takeovers in Highly Automated Driving

Abstract: This driving simulator study, conducted as a part of Horizon2020-funded L3Pilot project, investigated how different car-following situations affected driver workload, within the context of vehicle automation. Electrocardiogram (ECG) and electrodermal activity (EDA)-based physiological metrics were used as objective indicators of workload, along with self-reported workload ratings. A total of 32 drivers were divided into two equal groups, based on whether they engaged in a non-driving related task (NDRT) during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Taken the above together, our result may indicate that being closer to the lead vehicle as well as changing the distance to abrupt values away from the mean may be accompanied by higher stress levels and unhealthy states for the driver as well as the passenger. These results are in line with very recent research showing that within a driving simulator, shorter time headways are associated with higher workloads, which might affect drivers' safety [67]. The fact that not only the average distance but also the standard deviation of distance has an impact on drivers' HR highlights the importance of connected vehicles where the distance can be calibrated and kept constant based on different user profiles.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Taken the above together, our result may indicate that being closer to the lead vehicle as well as changing the distance to abrupt values away from the mean may be accompanied by higher stress levels and unhealthy states for the driver as well as the passenger. These results are in line with very recent research showing that within a driving simulator, shorter time headways are associated with higher workloads, which might affect drivers' safety [67]. The fact that not only the average distance but also the standard deviation of distance has an impact on drivers' HR highlights the importance of connected vehicles where the distance can be calibrated and kept constant based on different user profiles.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, [6] showed that within a simulated platooning scenario, drivers' mental stress measured through biosignals increased as the distance to the lead vehicle decreased. Another very recent study performed in a driving simulator found out that drivers' workload was higher during a shorter time headway [7].…”
Section: Introductionmentioning
confidence: 96%